Integrasi Good Corporate Governance (GCG) Berbasis Emotional Spiritual Quotient (ESQ) Dalam Meningkatkan Kinerja Karyawan Lembaga Amil Zakat - Choirunisa, Anggita`; Faiza, Nurlaili Adkhi Rizfa; Sadiq Ibrahim Mijinyawa (Istithmar, 2025)
Good Corporate Governance (GCG) is a key element in modern organizational management, yet the integration of Emotional and Spiritual Quotient (ESQ) also plays a crucial role in enhancing organizational performance. This study aims to analyze the integration of ESQ-based GCG at LAZISMU Kota Madiun and its impact on employee performance. Using a qualitative method with a field research approach, the study finds that ESQ-based GCG is implemented through five core principles: transparency, accountability, professionalism, fairness, and responsibility. This integration promotes the internalization of integrity, transparency, and moral responsibility, combined with emotional and spiritual intelligence. As a result, the work environment becomes more supportive of employees’ psychological and ethical well-being. Performance, measured in terms of quantity, quality, and timeliness, indicates that employees actively participate in social and religious activities, perform duties with strong spiritual values, and complete tasks efficiently and responsibly.